Reconsidering hḳṭn in 1 Samuel 16.11 - Aviʿoz, Mikhaʾel (Biblische Zeitschrift, 2024)
This paper offers a new understanding of the word הקטן regarding David in 1 Samuel 16. Instead of focusing on David’s young age, the paper suggests focusing on his height, an understanding that is supported by various details in Samuel as well as in biblical and post-biblical literature.